2021
DOI: 10.1039/d1na00044f
|View full text |Cite
|
Sign up to set email alerts
|

Aerogels are not regulated as nanomaterials, but can be assessed by tiered testing and grouping strategies for nanomaterials

Abstract: Aerogels contribute to an increasing number of novel applications due to many unique properties, such as high porosity and low density. They outperform most other insulation materials, and some are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 65 publications
(99 reference statements)
1
18
0
Order By: Relevance
“…61 Hazard screenings on released fragments is possible and relevant, as demonstrated on the example of organic aerogels. 62 • If not nano-enabled but consisting of particles (lower right quadrant in Fig. 2), the conventional dust issues are to be considered.…”
Section: Environmental Science: Nano Papermentioning
confidence: 99%
See 1 more Smart Citation
“…61 Hazard screenings on released fragments is possible and relevant, as demonstrated on the example of organic aerogels. 62 • If not nano-enabled but consisting of particles (lower right quadrant in Fig. 2), the conventional dust issues are to be considered.…”
Section: Environmental Science: Nano Papermentioning
confidence: 99%
“…aerogels are not nanomaterials by EU Commission's recommended definition and hence not considered nanomaterial in REACH, but the fragments that they potentially release during their use and end-of-life phases can be assessed by methods and tiered testing schemes developed for nanomaterials. 62,95 The AMEA recommendations close the assessment gap on this quadrant. 12 b) Many AdMa are not even nano-enabled.…”
Section: Comparison Of Amea To the Ongoing Work In The Oecd Wpmn "Ste...mentioning
confidence: 99%
“…155 Keller et al classify aerogels based on their safety profile. 175 They compared 19 aerogels consisting of organic aerogels, such as chitosan, cellulose, alginate, or polyurethane, and inorganic aerogels, such as pyrolyzed carbon or silicate. They just found polyurethane makes a temporary and reversible inflammation in the lung in Wistar rats.…”
Section: Potential Toxicity Induced By Hydrogelsmentioning
confidence: 99%
“…In a published workflow for aerogels testing, the group of Keller et al has shown the tiered testing strategy [11]; additional teams have applied the workflow in order to categorize and group nanomaterials [74][75][76].…”
Section: Safety Regulation In Aerogels Testingmentioning
confidence: 99%
“…The hazard assessment of aerogels has to take into account the fact that inhalable or ingestible fragments have components that can have toxicity characteristics matching the ones displayed by nanostructures [10]. Moreover, aerogels present a large surface area, so their potency resides in this extended functional surface [11]. Regardless, the testing strategy should follow the future use of the aerogel.…”
Section: Introductionmentioning
confidence: 99%